Care Management Trajectories of Infants with Life-Limiting Conditions Who Died Before 12 Months of age And Understanding How We Deliver Palliative Care - Iten, Rebecca (Curtin University, 2024)
The care of infants with life-limiting conditions is complex, complicated by uncertain prognosis, lengthy hospital stays, invasive procedures and the prospect of sudden deterioration and death. This thesis comprised of two studies: A retrospective study of infants with life-limiting conditions who died in three tertiary hospitals in Western Australia, and an integrative review of the literature to better understand how palliative care is delivered to infants and examine the involvement of specialist palliative care teams.